EFEK TEMPERATUR PIPA KAPILER TERHADAP KINERJA MESIN PENDINGIN - Anwar, Khairil; Arif, Effendy; Piarah, Wahyu H. (Jurnal MEKANIKAL, 2010)
The aims of this research are to obtain (1) the effect of the capillary tube temperature on the refrigerant condition and the refrigerating capacity in the refrigeration system and (2) the optimum temperature condition for obtain better system performance.This research was done in the Refrigeration System Laboratory at Tadulako University in Palu. The method applied in this research is an experimental method, with various temperature at capillary tube. Various temperature is obtained by placing capillary tube in freezer from other refrigeration system (refrigerator), through arrangement of thermostat.The result of this research indicates that decreasing cooling temperature of capillary tube causes refrigerating capacity and Coefficient of Performance of refrigeration system increases. Optimum performance of this examination during 30 minutes, obtained on the lowest thermostat temperature position that is â€“20Â°C ( position 7) with Coefficient of Performance (COP) of 2.71 Â